1996
DOI: 10.1097/00006123-199604000-00053
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peridural Scar and Recurrent Radicular Pain After Lumbar Discectomy: Magnetic Resonance Evaluation

Abstract: The purpose of this study was to investigate the presence of any correlation between recurrent radicular pain during the first six months following first surgery for herniated lumbar intervertebral disc and the amount of lumbar peridural fibrosis as defined by MR imaging. 197 patients who underwent first-time single-level unilateral discectomy for lumbar disc herniation were evaluated in a randomized, double-blind, controlled multicenter clinical trial. Clinical assessments, performed by physicians blinded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 25 publications
3
114
0
3
Order By: Relevance
“…The formation of postoperative epidural fibrosis is an inevitable result of laminectomy. Although the relationship between epidural fibrosis and clinical symptoms of FBSS has not been unequivocally proven, as many as 24% of all FBSS cases may be attributed to epidural scar adhesion [27].The mechanical tethering of nerve roots, or the dura, by the excessive formation of epidural fibrosis may be a contributing factor for a significant subset of patients suffering from FBSS [3,26,27]. However, several authors have reported that there are no important differences between symptomatic and asymptomatic patients in fibrosis demonstrated by computed tomography (CT) and magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of postoperative epidural fibrosis is an inevitable result of laminectomy. Although the relationship between epidural fibrosis and clinical symptoms of FBSS has not been unequivocally proven, as many as 24% of all FBSS cases may be attributed to epidural scar adhesion [27].The mechanical tethering of nerve roots, or the dura, by the excessive formation of epidural fibrosis may be a contributing factor for a significant subset of patients suffering from FBSS [3,26,27]. However, several authors have reported that there are no important differences between symptomatic and asymptomatic patients in fibrosis demonstrated by computed tomography (CT) and magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for FBSS include inadequate surgical decompression, recurrent disc herniation, lumbar instability, extensive epidural scar, and inadequate fusion [7]. The postoperative epidural scar can cause extradural compression or dural tethering, which results in recurrent radicular pain and physical impairment [27].…”
Section: Introductionmentioning
confidence: 99%
“…In accord with this, we found significantly less fibrosis in the laminotomy group than in the laminectomy group, and the grade of epidural fibrosis also increased over time, especially in the laminectomy group. However, the definite pathomechanism that lies between epidural fibrosis and neural dysfunction is still uncertain [14,21,22]. Many clinical reports rely on MRI studies to assess scar formation and spinal canal compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5 % to 24 % of all cases of FBSS were the results of epidural fibrosis [1,2,5] . Ross et al believe that for every 25 % increase in scarring, the risk of recurrent radicular pain increases 2.02 times [6] .…”
Section: Discussionmentioning
confidence: 99%